A study on comparison between substitution of low density polyethylene/plastic mix and ordinary mixes with various percentages of bitumen - Siti Robiah, Arshad (2017)
Asphalt use in road pavement because it’s very economical and fulfilled the roadway design requirement such as good riding quality, good skid resistance surface, quiet surface and low maintenance. However, consumption of asphalt has some weaknesses, as it become brittle and hard in cold weather and soft in hot weather hence it easy to crack. Besides that, an increase in traffic volume or capacity of the road users year by year is the one of the reasons of the pavement crack, defect and damage. Hard traffic and high loading weight by vehicles are also contributed to the pavement’s failure. Hence, to reduce the damage and defect, an improvised road or pavement structure is needed. This experiment will look into modified-bitumen where plastic or polyethylene will substitute the asphalt in various percentages. A total of 30 samples were prepared in laboratory with the proper method, apparatus and machines. The samples were prepared based on the production method of Marshall Mix specimens. The samples designed according to requirement for the aggregate course wearing 14 (ACW 14) by using JKR Standard. The range of bitumen content is 4- 6% from the weight of total aggregates. The plastic or polyethylene will substitute with the bitumen 4-8% from the weight of bitumen content. The plastic or polyethylene can improve the workability, durability and save the bitumen used. Furthermore, it gave the good binding to aggregates and provide the high quality pavement for future. This finding gave the eco environmental friendly structure, which is the recycle plastic are used and save budget for the highway construction and maintenance. In the future, hopefully this finding can encourage new research to be conducted in the different ways and usage.